Organização e funcionamento do atendimento educacional especializado na educação infantil: estudo de caso - Amorim, Gabriely Cabestré [UNESP] (2015)
The Educational Service Specialist (ESA) in its new organizational structure format, is an issue that has been studied frequently, especially in the aspects of teaching and instrumental practice in Multifunction Resource Rooms (SRMs). However, there are few studies that address the organizational arrangements experienced in different and varied areas of the country. In this context, the aim of this study was to describe, from the perspective of educational administration and teachers, standards and organizational arrangements that structure ESA practice in early childhood education (EI), with the following objectives: a) identify the organizational structure the ESA favors the complementarity of actions in the common class; b) identify whether the ESA's organizational structure provides opportunity for coordination between the health and education and c) identify whether the actions of the ESA vary depending on training and experience time professor and disability. This is a descriptive nature of research, study type of case, held in a city in the interior that has agreements with community institutions offering multidisciplinary care and clinical teaching in the period from June to December 2013. The study included two professionals responsible for management (GE) of the ESA; 17 itinerant teachers of the ESA (PI) in the EI; nine school teachers (PR). Was used as data collection instrument the semi-structured interview developed in three versions of scripts, one for each participant group. There was no significant correlation of variables, according to Spearman's test on the themes: teacher education, length of experience, partnership, type of disability, ESA's actions. The results indicated that the services performed by the PI have individual variations, there is no consensus as to the recognition of itinerant teaching and ESA mode. The organizational structure of the ESA, although it offers possibilities of contact between PR and the...